Introduction: Camp memories in Africa and beyond - Lingelbach, Jochen (Memory Studies, 2025)
Introducing the special issue on the memorialization of camps in Africa and beyond, this text discusses key questions of memory studies and the global history of encampment. Whatever their purpose, all camps are meant to be exceptional, transitory and temporary. Camps are often connected to contested histories and memorialization efforts by former inmates or others can lead to controversies and struggles over its interpretation. Building on a range of empirical examples from Africa and beyond, dealing with camps ranging from the most coercive to the benevolent and from the beginning of the twentieth century until today, this special issue invites a comparative, globally entangled and actor-centred view on camp memorialization.